Analisis Hubungan Pertumbuhan ekonomi dan Ekspor Indonesia ke china dengan pendekatan kausalitas Granger - Nur Budi Utama, Ahmad; Mustika, Candra (Jurnal Paradigma Ekonomika, 2022)
The purpose of this study is to analyze the causal relationship between economic growth and the value of Indonesia's exports to China, the type of data used in this study is secondary data with an annual time period from 1995 to 2020, the analytical tool used in this study is the Granger causality test. Based on the results of the Granger causality test, it shows that there is no unidirectional or two-way relationship between economic growth and exports to China, so it can be concluded that economic growth and exports to China do not have a unidirectional or two-way causal relationship.